Urban Transformations in the Late Antique West: Materials, Agents, and Models - Neil Christie (Classica Digitalia: Humanitas Supplementum - Estudos Monográficos, 2020)
This volume is the fruit of a highly productive international research gathering academic and professional (field- and museum) colleagues to discuss new results and approaches, recent finds and alternative theoretical assessments of the period of transition and transformation of classical towns in Late Antiquity. Experts from an array of modern countries attended and presented to help compare and contrast critically archaeologies of diverse regions and to debate the qualities of the archaeology and the current modes of study. While a number of papers inevitably focused on evidence available for both Spain and Portugal, we were delighted to have a spread of contributions that extended the picture to other territories in the Late Roman West and Mediterranean. The emphasis was very much on the images presented by archaeology (rescue and research works, recent and past), but textual data were also brought into play by various contributors.